The employment of UV-spectroscopy combined with multivariate calibration for analysis of paracetamol, Propyphenazone and caffeine - Abdul Rohman; Arief Dzulfianto; Florentinus Dika Octa Riswanto (Indonesian Journal of Pharmacy, 2017)
The reference method for simultaneous analysis of drugs is chromatography, however, this technique is expensive, complex, and needs excessive sample preparation; therefore, some simple methods like UV spectroscopy is proposed. Assisted with multivariate calibration, it is possible to analyze drugs using UV spectroscopy without prior separation. This study is intended to use UV spectroscopy coupled with multivariate calibration of partial least square (PLS) for simultaneous analysis of paracetamol (PCT), propyphenazone (PROPI), and caffeine (CAFF) in tablet dosage form. The calibration model is prepared by developing a series 20 mixture of PCT, PROPI and CAFF with certain composition randomly and its absorbance is measured at wavelength of 220-313 nm with an interval of 3 nm. The performance of calibration model was assessed by coefficient of determination (R2), root mean square error of calibration (RMSEC) and root mean square error of cross validation (RMSECV). The R2 values for the correlation between actual values of PCT, PROPI and CAFF and predicted values using UV-spectroscopy combined with PLS are 0.9994; 0.9878; and 0.9919, respectively. The calibration errors expressed with RMSEC are 0.027%, 0.082% and 0.043% for PCT, PROPI and CAFF, respectively. While, during cross validation using “leave one out” technique, RMSECV values obtained are 0.062%, 0.095% and 0.982%, respectively for PCT, PROPI and CAFF. The level of drugs obtained are 226.76 ± 14.49 mg/tablet (equivalent to 90.70% from labeled claim) for PCT,  135.74 ± 11.23 mg/tablet (equivalent to 90.49% from labeled claim) for PROPI and 51.69 ± 2.35 mg/tablet (equivalent to 103.38% from labeled claim) for CAFF.